Characterization of accessions and species of Macadamia to stem infection by Phytophthora cinnamomi. (24th June 2016) - Akinsanmi, O. A.; Neal, J.; Drenth, A.; Topp, B.
Abstract : Phytophthora cinnamomi is a major pathogen in most macadamia plantations worldwide. Due to stem lesions, stem cankers and leaf defoliation, it results in loss of productivity and tree death. This study examined accessions of the four Macadamia species and their hybrids, produced via rooted stem cuttings or germinated seeds, for susceptibility to stem canker and necrotic lesions caused by P. cinnamomi . Plants were wound‐inoculated with agar containing P. cinnamomi . The symptoms produced in inoculated plants were used to characterize host susceptibility variation within and among the population. Lesion length and severity of stem canker were recorded. The four species and hybrids differed significantly in stem canker severity ( P  <   0.001) and lesion length ( P  =   0.04). Macadamia integrifolia and M. tetraphylla hybrids were the most susceptible. Macadamia integrifolia had the greatest stem canker severity and the most extensive lesions above and below the site of inoculation. Restricted lesion sizes were observed in M. ternifolia and M.    jansenii . The effects of basal stem diameter and the method of propagation either from cuttings or from seed were not significant. The genetic variation in the reaction of macadamia accessions to stem infection by P. cinnamomi is discussed.